An Impact of Exchange Rate on Export in Nepal - Joshi, Uttam Lal; Paudel, Krishna Prasad; Neupane, Rajan; Pathak, Pabitra (International Research Journal of MMC, 2023)
This study examines the short-run and long-run co-integration of theexchange rate on export of Nepal. Data are extracted from the published source of World Bank from 1975 to 2020. ARDL Bounds test is applied to test the co-integration after the test of unit root. The dependent variable is export and the independent variables are exchange rate, import, money supply and GDP.Augmented Dickey- Fuller test shows the variables are in the order of I(1) where the error correction term is negative and significant. The results show there is long- run co-integrationand the study also supports the short-run dynamic relationship between the dependent and independent variables that show the long-run and short-run impact of exchange rate on export of Nepal.So, the policy makers should focus on increasing export and reducing import and its sound exchange rate policy.